Validation of the CRAVE-C scale in Chinese adults: a four-study examination of competing motivations for physical activity versus rest - Cheng, Zhihui; Taylor, Alyx; Stults-Kolehmainen, Matthew A.; Gerber, Markus; Herold, Fabian; Ross, Michael; Ash, Garrett; Kramer, Arthur F.; Zhao, Mengxian (Frontiers in Psychology, 2024)
Background：The study aimed to validate the Cravings for Rest and Volitional Energy Expenditure (CRAVE) scale among Chinese adults with different health conditions (healthy control, chronic illnesses, and psychiatric disorders) and skill levels (athletes vs. non-athletes).Methods：In Study 1, a confirmatory factor analysis (CFA) using the Maximum Likelihood Method (MLM) was performed on a Chinese sample of emerging adults (N = 481) to evaluate the structural validity of the Cravings for Rest and Volitional Energy Expenditure-Chinese version (CRAVE-C). In Study 2, differences in "Move" and "Rest" desires were examined among patients with psychiatric disorders, patients with chronic illnesses, and healthy controls. In study 3, investigated the relationship between cardiorespiratory fitness and exercise motivation using the CRAVE-C (N = 83).In Study 4, the changes in "Move" desire from baseline to post-training were compared between athletes and non-athletes. Results：Results from Study 1 indicated that the 10-item CRAVE-C showed good fit indices (Chi² (34) = 118.769, CFI = 0.95, TLI = 0.934, SRMR = 0.053, RMSEA = 0.072). "Move" positively correlated with various factors of the Affective Exercise Experiences Questionnaire-Chinese and the Physical Effort Scale-Chinese, while "Rest" correlated negatively. In Study 2, Patients with psychiatric disorders had a significantly higher "Move" desire than healthy controls. Patients with chronic illnesses had a significantly higher "Rest" desire than healthy controls. In Study 3, higher cardiorespiratory fitness was associated with a slight increase in "Move" desire (3.26% ± 37.35%) and a decrease in "Rest" desire (18.94% ± 66.99%). Lower fitness was linked to a significant decline in "Move" desire (-54.61% ± 111.33%) and an increase in "Rest" desire (43.62% ± 63.64%). In Study 4, the athlete group demonstrated a significant increase in "Move" desire from baseline to post-training, whereas the non-athlete group reported a significant decrease in "Move" desire from baseline to post-training.Conclusion：The 10-item CRAVE-C has good reliability and validity in the Chinese cultural context and can be used among Chinese adults with different health conditions and skill levels.